Prevalence of hepatitis C virus infection in India: a systematic review - Chandra, Mahesh; Ahmad Paray, Ansar; Arora, Kunal (International Journal of Research in Medical Sciences, 2024)
HIV/AIDS, malaria, and tuberculosis are the three major infectious diseases that are equivalent to viral hepatitis. The existing research distinguishes between states within the Indian region to study the spread of hepatitis C. The factors that lead to the spread of the hepatitis C virus (HCV) and community-based complex interventions in public health are strongly correlated in this review. The main purpose of this study was to summarize the prevalence of the HCV in India from original research articles published from January 2004 to March 2024. We conducted a systematic search on Web of Science, Science Direct, PubMed, Scopus, Google Scholar, Medline, and other open-access journals. We evaluated all relevant papers that investigated the prevalence of the HCV. Finally, 20 studies on viral hepatitis published from January 2004 to March 2024 have been selected. Twenty full text publications were obtained and evaluated consisting of 117,661 research participants. Out of 117,661 participants, 3,811 were positive for HCV. Prevalence of hepatitis C was found 3.23%. Most of the male participants were affected by HCV as compared to Females. Blood transfusion, history of intravenous drugs, hospital admission, heterosexual contact, and history of surgeries, were the most common ways for people to contract HCV. To reduce the incidence of viral hepatitis and eradicate the illness, effective public health initiatives are desperately needed. The review's recommendations include creating a uniform public health framework for primary care professionals serving both urban and rural populations, preventing the spread of infectious blood, and appropriately screening high-risk individuals.